Semantic similarity information discrimination for video captioning. (1st March 2023) - Du, Sen; Zhu, Hong; Xiong, Ge; Lin, Guangfeng; Wang, Dong; Shi, Jing; Wang, Jing; Xing, Nan
Abstract: Video captioning is a task that aims to automatically describe objects and their actions in videos using natural language sentences. The correct understanding of vision and language information is critical for video captioning tasks. Many existing methods usually fuse different features to generate sentences. However, the sentences have many improper nouns and verbs. Inspired by the successes of fine-grained visual recognition, we treat the problem of improper words to discriminate semantic similarity information. In this paper, we designed a semantic bilinear block (SBB) to widen the gap between the probability of existing and nonexistent words, which can capture more fine-grained features to discriminate semantic information. Moreover, our designed linear attention block (LAB) implements the channelwise attention for the 1-D feature by simplifying the squeeze-and-excitation structure. Furthermore, we designed a semantic discrimination network (SDN) that integrates the LAB and SBB into video encoder and decoder to leverage successful channelwise attention and discriminate semantic similarity information for better video captioning. Experiments on two widely used datasets, MSVD and MSR-VTT, demonstrate that our proposed SDN can achieve better performance than state-of-the-art methods. Highlights: We propose a semantic discrimination network (SDN) for video captioning. Visual tags are introduced to bridge the gap between vision and language. Build a semantic bilinear block to distinguish similar but not identical vision tag. Experimental results show that our model is superior to the state-of-the-art methods.